2017
DOI: 10.1039/c6sc04547b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics and charge transport in organic semiconductors: a classical approach to modeling electron transfer

Abstract: Using ab initio calculations of charges in PCBM fullerenes, a multiscale approach applies classical molecular dynamics to model charge transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
1
6
0
Order By: Relevance
“…The PBE functional (Perdew et al, 1996) was used for transfer integral calculations for computational efficiency (Baumeier et al, 2010). We previously showed (Pal et al, 2017) that this approach results in electron transfer rate for C60 in good agreement with available experimental and computational data reported elsewhere (Günes et al, 2007;Grzegorczyk et al, 2010;Ferguson et al, 2011;Nardes et al, 2012Nardes et al, , 2014Arntsen et al, 2013;Pelzer et al, 2017).…”
Section: Methodssupporting
confidence: 70%
“…The PBE functional (Perdew et al, 1996) was used for transfer integral calculations for computational efficiency (Baumeier et al, 2010). We previously showed (Pal et al, 2017) that this approach results in electron transfer rate for C60 in good agreement with available experimental and computational data reported elsewhere (Günes et al, 2007;Grzegorczyk et al, 2010;Ferguson et al, 2011;Nardes et al, 2012Nardes et al, , 2014Arntsen et al, 2013;Pelzer et al, 2017).…”
Section: Methodssupporting
confidence: 70%
“…where k =charge transfer rate, V c =direct effective electron coupling, and λ =reorganization energy of the system, see the Supporting Information for more details . By applying the Einstein relation ( μ = eD / k B T , D = kL 2 /2, where μ =mobility of charge transfer carriers, D= diffusion constant, L =mean length of particle movement) and assuming an equal number of charge carriers in different packing motifs, we estimated the conductivity value ratio as a ratio of the corresponding k values.…”
Section: Methodsmentioning
confidence: 99%
“…where k = charge transfer rate, V c = direct effective electron coupling,and l = reorganization energy of the system, see the Supporting Information for more details. [44,45] By applying the Einstein relation (m = eD/k B T, D = kL 2 /2, where m = mobility of charge transfer carriers, D = diffusion constant, L = mean length of particle movement) and assuming an equal number of charge carriers in different packing motifs,w ee stimated the conductivity value ratio as aratio of the corresponding k values.W ithin this model, we found that as hift from noncolumnar organization to aone-dimensional corannulene stack could result in ac irca 42-fold increase in conductivity values (see the Supporting Information for adetailed description). Therefore,t he experimentally observed conductivity enhancement could be attributed not only to the pB integration and/or D-A corannulene-host communication Figure 4.…”
Section: Angewandte Chemiementioning
confidence: 99%